Clinical and Echocardiographic Outcomes Following Permanent Pacemaker Implantation After Transcatheter Aortic Valve Replacement: Meta-Analysis and Meta-Regression. (July 2017) - Mohananey, Divyanshu; Jobanputra, Yash; Kumar, Arnav; Krishnaswamy, Amar; Mick, Stephanie; White, Jonathon M.; Kapadia, Samir R.
Abstract : Background—: Transcatheter aortic valve replacement has become the procedure of choice for inoperable, high-risk, and many intermediate-risk patients with aortic stenosis. Conduction abnormalities are a common finding after transcatheter aortic valve replacement and often result in permanent pacemaker (PPM) implantation. Data pertaining to the clinical impact of PPM implantation are controversial. We used meta-analysis techniques to summarize the effect of PPM implantation on clinical and echocardiographic outcomes after transcatheter aortic valve replacement. Methods and Results—: Data were summarized as Mantel–Haenszel relative risk (RR) and 95% confidence intervals (CIs) for dichotomous variables and as standardized mean difference and 95% CI for continuous variables We used the Higgins I 2 statistic to evaluate heterogeneity. We found that patients with and without PPM have similar all-cause mortality (RR, 0.85; 95% CI, 0.70–1.03), cardiovascular mortality (RR, 0.84; 95% CI, 0.59–1.18), myocardial infarction (RR, 0.47; 95% CI, 0.20–1.11), and stroke (RR, 1.26; 95% CI, 0.70–2.26) at 30 days. The groups were also comparable in all-cause mortality (RR, 1.03; 95% CI, 0.92–1.16), cardiovascular mortality (RR, 0.69; 95% CI, 0.39–1.24), myocardial infarction (RR, 0.58; 95% CI, 0.30–1.13), and stroke (RR, 0.70; 95% CI, 0.47–1.04) at 1 year. We observed that the improvement in left ventricular ejection fraction was significantly greater in the patients without PPM (standardized mean difference, 0.22; 95% CI, 0.12–0.32). Conclusions—: PPM implantation is not associated with increased risk of all-cause mortality, cardiovascular mortality, stroke, or myocardial infarction both at short- and long-term follow-up. However, PPM is associated with impaired left ventricular ejection fraction recovery post-transcatheter aortic valve replacement. Abstract : Supplemental Digital Content is available in the text.